Distributed star formation throughout the Galactic center cloud Sgr B2 - Ginsburg, Adam; Beuther, Henrik; Henshaw, Jonathan D.; Kruijssen, Diederik (Arxiv, 2018)
We report ALMA observations with resolution $≈0.5$" at 3 mm of the extended Sgr B2 cloud in the Central Molecular Zone (CMZ). We detect 271 compact sources, most of which are smaller than 5000 AU. By ruling out alternative possibilities, we conclude that these sources consist of a mix of hypercompact HII regions and young stellar objects (YSOs). Most of the newly-detected sources are YSOs with gas envelopes which, based on their luminosities, must contain objects with stellar masses $M_*\gtrsim8$ M$_\odot$. Their spatial distribution spread over a $\sim12×3$ pc region demonstrates that Sgr B2 is experiencing an extended star formation event, not just an isolated `starburst' within the protocluster regions. Using this new sample, we examine star formation thresholds and surface density relations in Sgr B2. While all of the YSOs reside in regions of high column density ($N(H_2)\gtrsim2×10^{23}$ cm$^{-2}$), not all regions of high column density contain YSOs. The observed column density threshold for star formation is substantially higher than that in solar vicinity clouds, implying either that high-mass star formation requires a higher column density or that any star formation threshold in the CMZ must be higher than in nearby clouds. The relation between the surface density of gas and stars is incompatible with extrapolations from local clouds, and instead stellar densities in Sgr B2 follow a linear $Σ_*-Σ_{gas}$ relation, shallower than that observed in local clouds. Together, these points suggest that a higher volume density threshold is required to explain star formation in CMZ clouds.
Version 1 vom 15. Januar 2018, vorläufige Fassung vom 17. Januar 2018
Gesehen am 22.11.2022